2020
DOI: 10.1093/zoolinnean/zlz164
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of morphological diversification in giant Berberomeloe blister beetles (Coleoptera: Meloidae) reveal an unexpected taxonomic diversity concordant with mtDNA phylogenetic structure

Abstract: Delimiting species boundaries is a complex challenge usually hindered by overlooked morphological diversification or misinterpretation of geographically structured phenotypic variability. Independent molecular data are extremely useful to characterize and understand such morphological diversity. Morphological and molecular variability of the non-phoretic and apterous, widely distributed, giant blister beetles of the genus Berberomeloe, were investigated within and between lineages across most of the distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 149 publications
0
25
0
Order By: Relevance
“…These evident patterns of morphological differentiation within M. ramburii, M. gibbulus, and M. goudotii may reflect a relatively recent history of isolation across populations, probably consequence of the existence of multiple isolated Pleistocene refugia (Abellán and Svenning 2014), as proposed for other flightless Iberian Coleoptera (Sánchez-Vialas et al 2020). In any case, these hypotheses require phylogeographic analyses to be properly tested.…”
Section: 2 -mentioning
confidence: 95%
“…These evident patterns of morphological differentiation within M. ramburii, M. gibbulus, and M. goudotii may reflect a relatively recent history of isolation across populations, probably consequence of the existence of multiple isolated Pleistocene refugia (Abellán and Svenning 2014), as proposed for other flightless Iberian Coleoptera (Sánchez-Vialas et al 2020). In any case, these hypotheses require phylogeographic analyses to be properly tested.…”
Section: 2 -mentioning
confidence: 95%
“…Deciding a taxonomical status based on minute morphological differences may be incorrect. This is because intraspecific phenotypic polymorphism may occur which is common in many species (Sánchez-Vialas et al, 2020;Yeong et al, 2018). In Lampyridae research, intraspecific variation was observed, such as the pronotum colour of Pteroptyx bearni from West versus East Malaysia and Pt.…”
Section: Resultsmentioning
confidence: 99%
“…To delimit species, we adopted the evolutionary species concept ( Wiley 1978 ; Wiley and Mayden 2000 ) in which a species is considered “a single lineage of ancestral descendant populations of organisms which maintains its identity from other such lineages and which has its own evolutionary tendencies and historical fate” ( Wiley 1978 : 18). This concept combines implications derived from the phylogenetic species concept, such as reciprocal monophyly, with additional subjective properties (e.g., phenetic distinguishability and reproductive isolation, among other lines of evidence) that can be used to assess the historical fate of lineages ( Ruiz and García-París 2015 ; Sánchez-Vialas et al 2020 ).…”
Section: Materials and Methodsmentioning
confidence: 99%